PERMASALAHAN UMUM DAN KHUSUS DI DESA SIHEMUN BARU: TANTANGAN DAN SOLUSI UNTUK PENDIDIKAN, KESEHATAN, EKONOMI, PEMERINTAHAN, KEAMANAN, DAN INFRASTRUKTUR - Rizki Christian Sipayung; Ego Devani Tanjung; Sitompul, Owen Dipadry; Alpori Omega Pasaribu (Jurnal Visi Eksakta, 2023)
Community Service offers a variety of benefits for students, communities, local governments, and universities. For students, dedication is a means to apply the knowledge gained on campus, build confidence, strengthen mentality, and develop creativity and innovation. Students also gain direct experience in the field, increase their insight, and mature their mindset as the next generation. For the community, the presence of service students provides energy and thought assistance in planning and implementing development programs, as well as improving critical thinking skills and solving daily problems. For local governments, this program establishes good cooperation with students, as well as getting energy assistance to implement various programs. Higher education also benefits by being able to focus more on developing science and technology, developing teaching practices through real cases, and building cooperation with various parties. Overall, service is an important means in realizing service for university personnel and disseminating knowledge for the benefit of the wider community.